2010
DOI: 10.1158/1535-7163.mct-09-0938
|View full text |Cite
|
Sign up to set email alerts
|

The Preclinical Pharmacology and Therapeutic Activity of the Novel CHK1 Inhibitor SAR-020106

Abstract: Genotoxic antitumor agents continue to be the mainstay of current cancer chemotherapy. These drugs cause DNA damage and activate numerous cell cycle checkpoints facilitating DNA repair and the maintenance of genomic integrity. Most human tumors lack functional p53 and consequently have compromised G 1 -S checkpoint control. This has led to the hypothesis that S and G 2 -M checkpoint abrogation may selectively enhance genotoxic cell killing in a p53-deficient background, as normal cells would be rescued at the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
84
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(94 citation statements)
references
References 44 publications
10
84
0
Order By: Relevance
“…Cells were harvested, lysates prepared, protein estimations conducted, and Western blots undertaken as described (18), using the following antibodies: pSer473 AKT, AKT, pSer9 GSK3b, GSK3b, pSer235/236 S6 ribosomal protein (S6RP), S6RP, pSer330 NDRG, NDRG, pSer157 VASP, VASP, pSer19 MLC2, MLC2, pThr24 FOX01/pThr32 FOX03a, FOX01, PRAS40, cleaved PARP, IRS2, pThr1135 Rictor, Rictor, cyclin E2, c-MYC (Cell Signaling Technology), PIK3IP1 (Abcam), pThr246 PRAS40 (Upstate), cleaved caspase-3 (Epitomics), cyclin D1, p27, and glyceraldehyde-3-phosphate dehydrogenase (GAPDH; Neomarkers).…”
Section: Protein Immunoblotting and Immunoassaymentioning
confidence: 99%
See 1 more Smart Citation
“…Cells were harvested, lysates prepared, protein estimations conducted, and Western blots undertaken as described (18), using the following antibodies: pSer473 AKT, AKT, pSer9 GSK3b, GSK3b, pSer235/236 S6 ribosomal protein (S6RP), S6RP, pSer330 NDRG, NDRG, pSer157 VASP, VASP, pSer19 MLC2, MLC2, pThr24 FOX01/pThr32 FOX03a, FOX01, PRAS40, cleaved PARP, IRS2, pThr1135 Rictor, Rictor, cyclin E2, c-MYC (Cell Signaling Technology), PIK3IP1 (Abcam), pThr246 PRAS40 (Upstate), cleaved caspase-3 (Epitomics), cyclin D1, p27, and glyceraldehyde-3-phosphate dehydrogenase (GAPDH; Neomarkers).…”
Section: Protein Immunoblotting and Immunoassaymentioning
confidence: 99%
“…iodide as described and analyzed by flow cytometry (18). The proportion of cells in each phase of the cell cycle was determined using either the Cell Quest Pro Software package (BD Biosciences) or WinMDI 2.8.…”
Section: Translational Relevancementioning
confidence: 99%
“…It has been suggested that abrogating the G 2 checkpoint may increase the efficacy of genotoxic agents preferentially in p53-deficient backgrounds, as normal tissue would be rescued at the p53-dependent G 1 /S checkpoint (3,9,10). There is increasing evidence that this is the case for inhibitors of CHK1 (11)(12)(13)(14)(15)(16), but the case for CHK2 is still unclear and may depend on the cell line and cytotoxic agent employed (17)(18)(19)(20)(21)(22)(23). However, in cells that possess a functional p53 pathway, there is evidence that CHK2 inhibitors protect against apoptosis induced by ionizing radiation (IR) and taxol (21,(24)(25)(26)(27), presumably by blocking CHK2-dependent activation of p53.…”
Section: Introductionmentioning
confidence: 99%
“…Abrogation of the G 2 checkpoint (by Chk1 inhibition and other strategies) has been shown to preferentially sensitize p53 mutant tumor cells to chemotherapy and radiation. [10][11][12][13][14][15][16][17] The prevailing model for tumor cell selectivity of Chk1 inhibition is that tumor cells harbor aberrations in other DNA damage response machinery (i.e., p53, p16, Rb) and, thus, do not G 1 arrest in response to DNA damage leading to selective sensitization of tumor cells by Chk1 inhibition, while normal cells are protected from Chk1 inhibition by their other intact checkpoints (i.e., p53-mediated G 1 arrest).…”
Section: Introductionmentioning
confidence: 99%